Cellulosic biocomposites: Potential materials for future - Bhat, A.H. (Springer Verlag, 2017)
Bionanocomposite is one of the remarkable achievements of nanotechnology in material science to replace conventional non-biodegradable petroleum based plastics for packaging applications. In general, bionanocomposites are made up of biodegradable polymers (biopolymers) and bio based reinforcing material in the size range of 10-100 nm in one or more dimensions. Bio based materials could provide a solution for petroleum shortage and waste management problems. One of the potential reinforcing agents is agro industrial based is cellulose. Such composites demonstrate improved properties as compared to the neat biopolymers due the large surface area and high aspect ratio of nanoparticles. This study has given a clear overview of nanocellulose based composites by describing their isolation, surface modification, composite preparation, properties, and applications. Furthermore, the obtained results for developed bionanocomposites materials shows that it can be a promising alternative for conventional packaging materials with improved properties. © Springer International Publishing AG 2017.